Undecylenic Acid Inhibits Morphogenesis of Candida albicans - McLain, Nealoo (American Society for Microbiology, 2000)
Resilient liners are frequently used to treat denture stomatitis, a condition often associated with Candida albicans infections. Of 10 liners tested, 2 were found to inhibit the switch from the yeast form to hyphae and a third was found to stimulate this switch. The inhibitor was determined to be undecylenic acid.